CADD-based discovery of novel oligomeric modulators of PKM2 with antitumor activity in aggressive human glioblastoma models - Maia Cabrera; Romina Armando; Ian Czarnowski; Patricio Chinestrad; Ramiro Blanco; Alejandra Zinni; Daniel Gómez; Diego L. Mengual Gómez; Pablo Lorenzano Menna (Heliyon)
Pyruvate kinase isoform M2 (PKM2) is a multifunctional enzyme capable of transitioning between monomeric, dimeric, and tetrameric states, with its oligomeric equilibrium playing a pivotal role in tumour progression and survival. The unique exon ten at the dimer-dimer interface represents an attractive target for isoform-specific modulation, offering opportunities for disrupting this equilibrium and altering tumour cell dynamics.This study identifies a novel druggable pocket at the PKM2 dimer interface through conformational analysis. This pocket was exploited in a virtual screening of a large small-molecule library, identifying two promising candidates, C599 and C998. Both compounds exhibited dose-dependent antiproliferative effects in glioblastoma cell lines and induced apoptosis, as evidenced by caspase 3/7 activation. These effects were directly linked to their inhibition of PKM2 enzymatic activity, validating the proposed mechanism of action in their rational design. ADMET studies further highlighted their strong potential as lead PKM2 inhibitors for GBM treatment.Molecular dynamics (MD) simulations and post-MD analyses, including Dynamic Cross-Correlation Maps (DCCM), Probability Density Function (PDF), and Free Energy Landscape (FEL), confirmed the stability of the protein-ligand interactions and highlighted critical residues at the dimer-dimer interface. The Steered MD simulations demonstrated the high affinity of the compounds for PKM2, as evidenced by the requirement of high rupture forces to induce an unbinding event. These results highlight the potential of the compounds as oligomeric modulators of PKM2. These findings position C599 and C998 as promising lead compounds for antitumor applications. Future studies will focus on optimising these candidates and assessing their efficacy in vivo glioblastoma models, reassuring the thoroughness of our research and the potential for further advancements.